Celebrating Ten Years of Arctic Review - Ravna, Øyvind; Bankes, Nigel (Arctic Review on Law and Politics, 2020)
This article presents the editors' introduction to the ten-year anniversary issue of Arctic Review on Law and Politics, with a history of the journal and an overview of the issue's contents.2020 represents a milestone for Arctic Review on Law and Politics as it is 10 years since the first, slender issue of the journal was launched at the university bookstore in Tromsø, Norway, on 14 April 2010. In a manner of speaking, the journal has left its innocent childhood and entered a more challenging adolescence. This anniversary year provides an opportunity to both look back in time and to present some thoughts about the future. It is also a golden opportunity to present an anniversary anthology of insightful articles.